Rasisme Institusi Dalam Novel The Hate U Give Karya Angie Thomas - Damayanti, Yanti (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2024)
This research is titled Institutional Racism in the novel The Hate U Give by Angie Thomas. The purpose of this study is to describe the form of institutional racism. This research method used qualitative description. The data source is from the novel The Hate U Give by Angie Thomas. The theories used include Bradway's qualitative descriptive theory (2018), Nurgiyantoro's character theory (1998), and Adams' institutional racism theory (2016). The results of this study are institutional racism including: a) police, b) law, and c) education. Institutional racism in the novel The Hate U Give is shown against Khalil Harris and Star Amara who is an African-American of black descent.